Peranan Kepemimpinan Kepala Madrasah dalam Peningkatan Mutu Pendidikan - Nana Suryapermana; Anis Fauzi; Inni Nihayah; Yahdinil Firda Nadhiroh (LPPM IAIN Sorong, 2022)
The results of a preliminary study show that on average the head of madrasah has less academic ability, lacks self-motivation, is less assertive in being a leader, is less able to influence and invite his subordinates to improve work ethic. This phenomenon is caused by the lack of competency, procedural, lack of transparency, many nuances, and internal and external factors of madrasah principals. Data collection techniques using interviews, observation and documentation. The data analysis technique uses the Miles and Huberman model. Miles and Huberman who argued that activities in qualitative data analysis were carried out interactively and carried out continuously until completion, so that the data was saturated. Activities carried out are data reduction, display data and conclusion drawing / verification. The results showed that the leadership role of the headmaster at MA Mathla'ul Anwar and MA Syekh Manshur is very important in improving the quality of education, because the head of the madrasah is a determining element in the direction of madrasah success and acts as a manager, leader, supervisor, educator, administrator, innovator, motivator.